RACE, GENDER AND CULTURE OF PANCHO FIERRO WATERCOLORS - Arrelucea Barrantes, Maribel (2011)
This article takes the watercolors of Pancho Fierro ask a historical source to enter the study of cultural unity and circularity, more than the different, bewteen the colonial society, order estates, and Republican in the first half of the ninetheenth Century.